Evolution of Antiphospholipid Syndrome - Arachchillage, Deepa R.J.; Pericleous, Charis (Seminars in Thrombosis and Hemostasis, 2023)
Antiphospholipid syndrome (APS) is an autoimmune prothrombotic disease characterized by thrombosis and/or pregnancy complications caused by antiphospholipid antibodies (aPL). The history of APS can be traced back to observations made during screening programs for syphilis conducted in the mid-20th century, with identification of patients with the so-called biological false-positive serological reactions for syphilis. Initial observation linking aPL with recurrent miscarriages was first reported more than 40 years ago. Since then, our understanding of the pathogenesis and management of APS has evolved markedly. Although APS is an autoimmune disease, anticoagulation mainly with vitamin K antagonists (VKAs) rather than immunomodulation, is the treatment of choice for thrombotic APS. Direct acting oral anticoagulants are inferior to VKAs, especially those with triple-positive APS and arterial thrombosis. Inflammation, complement activation, and thrombosis in the placenta may contribute to pathogenesis of obstetric APS. Heparin, mainly low-molecular-weight heparin, and low-dose aspirin represent the treatments of choice for women with obstetric complications. Increasingly, immunomodulatory agents such as hydroxychloroquine for thrombotic and obstetric APS are being used, especially in patients who are refractory to present standard treatment.
Keywords: antiphospholipid syndrome; antiphospholipid antibodies; thrombosis; obstetric complications; anticoagulation